Lipid biosynthesis of ten thraustochytrid strains isolated from mangrove Xuan Thuy, Nam Dinh - Đào, Phạm Thị Bích; Tuấn, Nguyễn Đình; Khoa, Trần Đăng; Huyên, Chử Thị; Thành, Đỗ Hoàng; Hà, Nguyễn Thị Hoài (Vietnam Journal of Biotechnology, 2016)
The features of polyunsaturated fatty acid-PUFA structures were corresponded to each separate functions as adjusting the cellular physiology and gene expression. Therefore, lack of PUFA could lead to abnormalities in skin, kidney, neural networks, immune responses and inflammation; cardiovascular, endocrine, respiratory and reproductive systems. In fish oil, PUFA content were low, thus it was difficult to produce on a large scale. Therefore, the exploration of PUFA sources particularly as arachidonic acid-AA, eicosapentaenoic acid EPA, docosapentaenoic acid-DPA/DHA attracted many researches. Heterotrophic microalgae Thraustochytrids were capable of producing high amounts of DHA and PUFA composition varied. DHA can be synthesized by the metabolism of AA, EPA and DPA. The different types of PUFA reflected relationships in classification. Ten heterotrophic microalgae thraustochytrids isolated from mangrove Xuan Thuy, Nam Dinh contain fatty acid composition varied from C12 to C28. Especially, they had two important fatty acids of PUFA as EPA and DPA. Polyunsaturated fatty acids - PUFA content of ten thraustochytrid strains were from 28.95 to 49.62% total lipid. DPA compared to other PUFA were high for all thraustochytrid strains studied, accounting 20.22 to 39.35% TFA. Ten thraustochytrid strains had the highest growth with carbon source as glucose, total lipid reached 7 to 12.35 % dry weight biomass after 72 hours. Growth rate and lipid biosynthesis in organic nitrogen source were higher than in inorganic nitrogen sources. The best source of nitrogen for growth and lipid biosynthesis of ten thraustochytrid strains is yeast extract, total lipid were 8.57 to 18.87% dry weight biomass after 72 hours